Thermophilic and cellulolytic consortium isolated from composting plants improves anaerobic digestion of cellulosic biomass: Toward a microbial resource management approach. (August 2015) - Kinet, R.; Destain, J.; Hiligsmann, S.; Thonart, P.; Delhalle, L.; Taminiau, B.; Daube, G.; Delvigne, F.
Highlights: Efficient anaerobic, thermophilic and cellulolytic consortium was isolated from compost. Consortium improves anaerobic digestion of cellulosic substrates. Main microbial strains are strictly anaerobic and belong to Clostridia class. Despite weak richness and evenness, consortium adapts to pH evolution. Abstract: A cellulolytic consortium was isolated from a composting plant in order to boost the initial hydrolysis step encountered in anaerobic digestion. Improvement of the cellulose degradation, as well as biogas production, was observed for the cultures inoculated with the exogenous consortium. Metagenomics analyses pointed out a weak richness (related to the number of OTUs) of the exogenous consortium induced by the selective pressure (cellulose as sole carbon source) met during the initial isolation steps. Main microbial strains determined were strictly anaerobic and belong to the Clostridia class. During cellulose anaerobic degradation, pH drop induced a strong modification of the microbial population. Despite the fact that richness and evenness were very weak, the exogenous consortium was able to adapt and to maintain the cellulolytic degradation potential. This important result point out the fact that simplified microbial communities could be used in order to increase the robustness of mixed cultures involved in environmental biotechnology.